Assessment of menopausal symptoms awareness among women in Bharatpur, Nepal - Panta, Aliza; Devi Dahal , Babita; Prasad Koirala , Hari (International Journal of Health, 2024)
Background: Menopause signifies the end of a woman's reproductive phase, characterized by the cessation of ovarian hormone production and the termination of menstrual cycles, typically occurring between the ages of 45 and 55. The transition involves a range of physical and psychological symptoms manifesting before, during, and after menopause. Method: This cross-sectional analytical study assessed the level of awareness regarding menopausal symptoms among women in Bharatpur-9, Chitwan. A non-probability sampling technique was used to select 257 respondents. Data were collected using a semi-structured interview schedule and analyzed with SPSS version 20.0. Results: Among the respondents, 53.3% were aged 40-49 years (Mean ± S.D.; 48.84 ± 6.27), and 69.3% experienced menarche between ages 13-15. A majority (59.9%) had not yet reached menopause. Knowledge of menopausal symptoms was as follows: joint pain (90.7%), sleep problems (90.7%), irritability (90.7%), hot flushes (22.2%), anxiety (22.2%), sadness (22.2%), vaginal dryness (22.6%), loss of interest in sex (25.7%), palpitations (18.7%), and decreased visual acuity (9.3%). Statistical significance was found between awareness levels and factors such as religion (p=0.00), ethnicity (p=0.00), educational status (p=0.006), family type (p=0.043), cessation of menstruation (p=0.013), and cause of menopause (p=0.00). Overall, 53.7% of respondents had average knowledge about menopausal symptoms. Conclusion: The study concluded that over half of the respondents possessed average awareness of menopausal symptoms. Hence, there is a need for women to receive correct and comprehensive information regarding menopausal symptoms and their management.